Faulkner and his contemporaries - Urgo, Joseph R.; Abadie, Ann J. (Faulkner and Yoknapatawpha., 2004)
Although he spent the bulk of his life in Oxford, Mississippi-far removed from the intellectual centers of modernism and the writers who created it-William Faulkner (1897-1962) proved to be one of the American novelists who most comprehensively grasped modernism. In his fiction he tested its tenets in the most startling and insightful ways. What, then, did such contemporaries as Ernest Hemingway, Eudora Welty, and Walker Evans think of his work? How did his times affect and accept what he wrote?. Faulkner and His Contemporaries explores the relationship between the Nobel laureate, ensconced in.